(untitled) (Journal of Engineering, 2023)
Adsorption and ion exchange are examples of fixed-bed sorption processes that show transient behavior. This means that differential equations are needed to design them. As a result, numerical methods are commonly utilized to solve these equations. The solution frequently used in analytical methods is called the Thomas solution. Thomas gave a complete solution that adds a nonlinear equilibrium relationship that depends on second-order reaction kinetics. A computational approach was devised to solve the Thomas model. The Thomas model’s validity was established by conducting three distinct sets of experiments. The first entails the adsorption of acetic acid from the air through the utilization of activated carbon. Following this, zeolite-5A adsorbs trichloroethylene (TCE) from the air. Finally, activated carbon is employed for the purpose of adsorbing o-cresol from aqueous solutions. A study was done to estimate phase equilibria and interphase mass transfer rates. To find the kinetic mass-transfer coefficient (K) for gases, the phase coefficients for mass transfer in the fluid phase ( ) and the pore phase ( ) were added together. The estimation of (K) for liquid was performed using the mass transfer coefficient for the solid phase and togather. The results suggest that the adsorption of acetic acid from air on activated carbon gives a good agreement with the Thomas model. The other sets of data demonstrate a disparity due to the underlying assumptions inherent in the Thomas model.